PERAN SERTA KENDALA ORANGTUA DALAM PROSES PENDAMPINGAN BELAJAR DI RUMAH DI ERA PANDEMI COVID-19 - Inekke Fatimatus Hasna; Imas Srinana Wardani; Apri Irianto (Jurnal Ilmiah Pendidikan Guru Sekolah Dasar, 2021)
Parenthood is one of the important responsibilities for nurturing, guiding, and educating children in order to explore their potential and form a good person. The purpose. of this study is to. describe the role of parents in accompanying the success of children's learning during the pandemic and to describe the obstacles parents encountered while accompanying home learning. The research uses a qualitative research approach with data collection techniques Interview, Documentation, Questionnaire Results of analysis of parental interview data in the process of parenthood in home learning mentoring has "good" criteria. As evidenced by the results of the questionnaire the role and constraints of, parents in the mentoring of learning .at home with "quite good", with some obstacles that exist. Constraints on the difficulty of understanding materials for parents who are against the background of low-level education criteria for children's learning. As well as the constraints of time sharing between work and accompanying children's learning at home at the parents of economic level criteria. The role of parents in accompanying home learning is very Influential. Because in the current condition parents are required to guide, provide support, and motivate the child to remain passionate in implementing. the online learnig process. Regardless of the circumstances of the parents, must still conditionthe time, energy and mind for the child. To deal with this condition, parents must also follow and improve their thinking and learning skills.